The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1124/jpet.110.167270
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inhibition of Carbonic Anhydrase IX Decreases Cell Proliferation and Induces Ceramide-Mediated Apoptosis in Human Cancer Cells

Abstract: Recently, carbonic anhydrase (CA) inhibitors have been proposed as a potential new class of antitumor agents. The aim of this study was to evaluate the antitumor activity of three CA inhibitors, namely acetazolamide (AZ) and two newly synthesized aromatic sulfonamides with high affinity for CA IX, 2-(4-sulfamoylphenyl-amino)-4,6-dichloro-1,3,5-triazine (TR1) and 4-[3-(N,N-dimethylaminopropyl)thioreidophenylsulfonylaminoethyl]benzenesulfonamide (GA15), against human tumor cells. The effects of AZ, TR1, and GA15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
71
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 30 publications
7
71
1
Order By: Relevance
“…Several studies suggested that cell death induced by intracellular acidosis can also be exploited for therapeutic purposes. For example, lowering of pH i by pharmacological inhibition of CAIX has been shown to activate ceramidemediated apoptosis in human cancer cells (43). This finding was corroborated by in vivo experiments where CAIX gene silencing led to a 40% reduction in xenograft tumor volume in mice (44).…”
Section: Discussionsupporting
confidence: 68%
“…Several studies suggested that cell death induced by intracellular acidosis can also be exploited for therapeutic purposes. For example, lowering of pH i by pharmacological inhibition of CAIX has been shown to activate ceramidemediated apoptosis in human cancer cells (43). This finding was corroborated by in vivo experiments where CAIX gene silencing led to a 40% reduction in xenograft tumor volume in mice (44).…”
Section: Discussionsupporting
confidence: 68%
“…Thus, it seems that the method and the timing used for measuring survival and proliferation is critical for the end results. The mechanisms for inhibiting cell survival by CAIX inhibitors are not well understood, but have previously been related to CAIX's role in maintaining a stable pHi in acidic environments [32][33][34] . To investigate if the reduced clonogenicity observed in HT29 cells was a result of such interference, pHi was measured.…”
mentioning
confidence: 99%
“…Recently, CA was demonstrated to support the pH homeostasis through controlling the intracellular proton level (Hulikova et al 2011), and its inhibition with CA inhibitors induces a state of intracellular acidification (Cianchi et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, many authors showed that CA inhibitors produced a drop in the intracellular pH of several cell lines (Cianchi et al 2010;Hulikova et al 2011). Interestingly, the tumor suppressor thioredoxin-interacting protein (TXNIP) is transcriptionally induced by stresses and stimuli, and some of them may act through modulating the intracellular pH (Chen et al 2010).…”
Section: Introductionmentioning
confidence: 99%